2020
DOI: 10.1007/s12015-020-10055-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Dynamics in Intestinal Epithelial Homeostasis: A Paradigm of Cell Fate Determination versus Cell Plasticity

Abstract: The rapid renewal of intestinal epithelium is mediated by a pool of stem cells, located at the bottom of crypts, giving rise to highly proliferative progenitor cells, which in turn differentiate during their migration along the villus. The equilibrium between renewal and differentiation is critical for establishment and maintenance of tissue homeostasis, and is regulated by signaling pathways (Wnt, Notch, Bmp…) and specific transcription factors (TCF4, CDX2…). Such regulation controls intestinal cell identitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…( 23 ) found that binding motifs for CDX2, HNF4a/g, and GATA 4/5/6 were enriched in 4575 ATAC-Seq peaks that are seen in intestine but not in other tissues. Among these, CDX2 is viewed as a master regulator of intestinal epithelial cell identity ( 24 ) that maintains a permissive chromatin environment that favorably influences the DNA binding of other TFs, for example, the intestine restricted TF HNF4a ( 25 ). Similarly, SMAD4 and HNF4 activate each other's expression and cobind to regulatory elements of intestinal differentiation genes to stabilize enterocyte identity ( 26 ), whereas other evidence shows that GATA4 is critical for gene expression in the proximal small intestine ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 23 ) found that binding motifs for CDX2, HNF4a/g, and GATA 4/5/6 were enriched in 4575 ATAC-Seq peaks that are seen in intestine but not in other tissues. Among these, CDX2 is viewed as a master regulator of intestinal epithelial cell identity ( 24 ) that maintains a permissive chromatin environment that favorably influences the DNA binding of other TFs, for example, the intestine restricted TF HNF4a ( 25 ). Similarly, SMAD4 and HNF4 activate each other's expression and cobind to regulatory elements of intestinal differentiation genes to stabilize enterocyte identity ( 26 ), whereas other evidence shows that GATA4 is critical for gene expression in the proximal small intestine ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Homeostasis of the intestinal epithelium requires coordinated interaction between numerous signaling pathways and transcription factors [ 43 ]. Cdx2 has been linked to regulation of expression of genes in the Notch signaling pathway [ 44 ], including Dll1 [ 13 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our observations lead to a model wherein Cdx impacts EphrinB1 expression and the CRC phenotype via a Notch-dependent mechanism (Figure 7). Homeostasis of the intestinal epithelium requires coordinated interaction between numerous signaling pathways and transcription factors [43]. Cdx2 has been linked to regulation of expression of genes in the Notch signaling pathway [44], including Dll1 [13,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin dynamics is crucial for organ development, including the control of proliferation, cell fate determination and tissue homeostasis, as well as for its plasticity and adaptive abilities to stresses (Rispal et al ., 2020). The role of chromatin components in the establishment of genetic programs controlling tissue homeostasis is a very partially explored field.…”
Section: Introductionmentioning
confidence: 99%